Overweight/Obese Schoolchildren with Low Muscle Strength Have a Lower Cardiorespiratory Capacity and Greater Cardiovascular Risk: Results of the School Health Survey of the Extreme South of Chile 2019 - Javier Albornoz-Guerrero; Rafael Zapata-Lamana; Daniel Reyes-Molina; Igor Cigarroa; Guillermo García Pérez de Sevilla; Sonia García-Merino (MDPI AG, 2021)
Objective: To compare cardiovascular risk and cardiorespiratory capacity in schoolchildren from a region in the extreme south of Chile according to nutritional status and muscular strength. Methods: An analytical cross-sectional study was performed on a sample of 594 schoolchildren from 5th to 8th grade in the extreme south of Chile. Based on body mass index and lower limb muscle strength, participants were divided into four groups: high strength-normal weight, high strength-overweight/obese, low strength-normal weight, and low strength-overweight/obese. Then, waist-to-height ratio and cardiorespiratory capacity, measured with the 20 m shuttle run test, were assessed to determine their cardiovascular risk, comparing the four groups. Results: The overweight/obese group with high muscular strength presented better indicators in anthropometric variables (waist circumference and waist-to-height ratio) than their peers with low muscular strength. Additionally, the overweight/obese group with low muscular strength presented a lower cardiorespiratory capacity than their peers with high muscular strength. Both results were observed in boys and girls. Conclusion: The results of this study suggest that overweight/obese schoolchildren with high muscle strength present healthier anthropometric indicators and greater cardiorespiratory capacity than their peers with low muscle strength. These results confirm the relevance of measuring muscle strength in schoolchildren and its usefulness to assess functionality. These results encourage the scientific community to continue studying the role that muscle strength plays in modulating the effects of overweight and obesity on respiratory and cardiovascular conditions in childhood.